Acceptance of COVID-19 boosters among hypertensive patients in China: A multicenter cross-sectional study - Ying Yan; Qingyuan Chen; Abudulimutailipu Nuermaimaiti; Yingzi Xiao; Le Chang; Huimin Ji; Huizhen Sun; Qinggang Song; Yuanfeng Gao; Junjie Xu; Lunan Wang (Human Vaccines & Immunotherapeutics)
Hypertension, a prevalent chronic disease, has been associated with increased COVID-19 severity. To promote the COVID-19 booster vaccination of hypertensive patients, this study investigated the willingness to receive boosters and the related influencing factors based on the health belief model (HBM model). Between June and October 2022, 453 valid questionnaires were collected across three Chinese cities. The willingness to receive a booster vaccination was 72.2%. The main factors that influenced the willingness of patients with hypertension to receive a booster shot were male (χ2 = 7.008, p = .008), residence in rural (χ2 = 4.778, p = .029), being in employment (χ2 = 7.232, p = .007), taking no or less antihypertensive medication (χ2 = 9.372, p = .025), with less hypertension-related comorbidities (χ2 = 35.888, p < .0001), and did not have any other chronic diseases (χ2 = 28.476, p < .0001). Amid the evolving COVID-19 landscape, the willingness to receive annual booster vaccination was 59.4%, and employment status (χ2 = 10.058, p = .002), and presence of other chronic diseases (χ2 = 14.256, p < .0001) are associated with the willingness of annual booster vaccination. Respondents with higher perceived severity, perceived benefits, perceived self-efficacy, and lower perceived barriers were more willing to receive booster shots. The mean and median value of willingness to pay (WTP) for a dose of booster were 53.17 CNY and 28.31 CNY. Concerns regarding booster safety and the need for professional advice were prevalent. Our findings highlight the importance of promoting booster safety knowledge and health-related management among hypertensive individuals through professional organizations and medical specialists.